Measuring and Managing a Salesperson's Future Value to the Firm - Kumar, V.; Sunder, Sarang; Leone, Robert P. (Journal of Marketing Research, 2014)
Research on sales force evaluation has mostly relied on reflective metrics such as sales volume, revenue, and manager evaluations to assess and manage a sales force. However, businesses are moving from a product-centric to a customer-centric view and from a backward-looking to a forward-looking strategic perspective, so sales organizations must adapt to the ever-changing marketplace to maximize performance. The authors propose a forward-looking and profit-oriented metric to evaluate and demonstrate the effects of training type and incentive type on a salesperson's future value. Using a latent class modeling approach, they identify two distinct segments in the sales force that exhibit different responses to varying levels of training and incentives. This suggests that a one-size-fits-all approach to sales force management may be suboptimal. Finally, the authors also evaluate the magnitude of the proposed effects in the short run as well as the long run and show that the magnitudes of the effects could vary depending on the time horizon being considered. The authors close with a discussion of the implications for research and practice, including sales force evaluation through customer relationship management–based heuristics and optimal training and incentive management.